Improvement of Methods of Processing Reliable Information in Managing Building and Construction Cadasters (Texas Journal of Engineering and Technology, 2023)
Carrying out the work on the basis of the developed instructions will help to solve a number of problems in the future. One of them is to create objective information about buildings and constructions. Because, the information of the state cadastre of buildings and constructions is initially formed basing on information about the technical parameters of the land plot, buildings and constructions in field conditions. In particular, the initial data will serve as a basis for the future. Therefore, it is very important to correctly form the data obtained in field conditions. For this, it is necessary to follow guidelines created and approved on the basis of established requirements